High‐level expression of STING restricts susceptibility to HBV by mediating type III IFN induction. Issue 2 (5th November 2018) - Dansako, Hiromichi; Imai, Hirotaka; Ueda, Youki; Satoh, Shinya; Shimotohno, Kunitada; Kato, Nobuyuki
Abstract: Hepatitis B virus (HBV) is a hepatotropic DNA virus causing hepatic diseases such as chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma. To study HBV, human hepatoma HepG2 cells are currently used as an HBV infectious cell culture model worldwide. HepG2 cells exhibit susceptibility to HBV by exogenously expressing sodium taurocholate cotransporting polypeptide (NTCP). We herein demonstrated that human immortalized hepatocyte NKNT‐3 cells exhibited susceptibility to HBV by exogenously expressing NTCP (NKNT‐3/NTCP cells). By comparing cyclic GMP‐AMP synthetase (cGAS)‐stimulator of interferon genes (STING) signaling pathway in several NKNT‐3/NTCP cell‐derived cell clones, we found that STING was highly expressed in cell clones exhibiting resistance but not susceptibility to HBV. High‐level expression of STING was implicated in HBV‐triggered induction of type III IFN and a pro‐inflammatory cytokine, IL‐6. In contrast, RNAi‐mediated knockdown of STING inhibited type III IFN induction and restored the levels of HBV total transcript in an HBV‐infected cell clone exhibiting resistance to HBV. These results suggest that STING regulates susceptibility to HBV by its expression levels. STING may thus be a novel target for anti‐HBV strategies.